Computer Engineering Students’ Learning Experiences in Online Classes - Mtshali, Thokozani Isaac; Mahlangu, Sizwe Marcus (Journal of Education Technology, 2025)
Learning Computer Engineering concepts and skills can be challenging for any first-time student enrolled in this course. The challenge can even be greater when instruction to the course is offered through online classes where a host of technical and internet bandwidth challenges are unavoidable. Therefore, this study was conducted to evaluate computer engineering students’ experiences in online classes in a South African university. Through a convergent parallel mixed method research approach, this study purposively sampled 63 computer engineering students. Data was collected through questionnaires and interviews. Data was analyzed statistically and thematically to solicit the comprehensive findings of the respondent’s experiences. The study found that 41% of computer engineering students experienced reduced peer interaction, 45% had difficulty understanding course content due to limited lecturer responsiveness, 51% reported concentration issues caused by technical delays, and 87% faced internet connectivity problems that disrupted their learning. These findings indicate that although online learning offers flexibility, it is not fully effective for a hands-on program like computer engineering. The lack of real-time interaction, practical engagement, and stable digital infrastructure significantly hindered students' ability to grasp complex concepts. Therefore, the study concludes that online platforms are not yet suitable for delivering technical courses without substantial improvements in instructional design and technological support.